INNOVATIVE APPROACHES TO EXPLAINING TOPICS IN MEDICAL BIOLOGY - Shodmanov , Bahtiyor Bakhromaliyevich; Alisherov , Temur Alisher ug‘li (Educational Research in Universal Sciences, 2023)
This article discusses various innovative approaches that can be employed by educators to teach medical biology topics in a more engaging and efficient manner. The author highlights the importance of visual aids, such as diagrams and infographics, in enhancing understanding and retention of complex concepts. The incorporation of multimedia resources, such as videos and animations, is also highlighted as a means to create a dynamic and interactive learning environment. Additionally, the integration of case studies, collaborative learning, gamification, personalized learning, and role play simulations are identified as effective strategies for enhancing comprehension and engagement. Overall, the article emphasizes the importance of embracing innovative teaching methods in medical biology classrooms to inspire a lifelong passion for learning among students.